2017
DOI: 10.1371/journal.pone.0188724
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thermostable alkaline proteases from Bacillus infantis SKS1 isolated from garden soil

Abstract: Proteases are one of the largest groups of hydrolytic enzymes constituting about 60% of total worldwide sales of industrial enzymes due to their wide applications in detergent, leather, textile, food and pharmaceutical industry. Microbial proteases have been preferred over animal and plant proteases because of their fundamental features and ease in production. Bacillus infantis SKS1, an alkaline protease producing bacteria has been isolated from garden soil of north India and identified using morphological, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…This result, in agreement with other reports ( Joshi et al., 2008 ), indicated that the highest amount of protease was secreted by the both bacterial isolates at alkaline pH. It is also reported that the maximum level of alkaline protease is produced by B. licheniformis MP1 at pH 8.0 ( Jellouli et al., 2011 ) and by B. circulans and B. infantis SKS1 at pH 10.0 ( Prakasham et al., 2005 ; Rao et al., 2009 ; Saggu and Mishra, 2017 ).
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…This result, in agreement with other reports ( Joshi et al., 2008 ), indicated that the highest amount of protease was secreted by the both bacterial isolates at alkaline pH. It is also reported that the maximum level of alkaline protease is produced by B. licheniformis MP1 at pH 8.0 ( Jellouli et al., 2011 ) and by B. circulans and B. infantis SKS1 at pH 10.0 ( Prakasham et al., 2005 ; Rao et al., 2009 ; Saggu and Mishra, 2017 ).
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The enzyme also has a significant role in many physiological and pathological processes i.e. protein catabolism, blood coagulation, zymogen activation and transport and secretion of proteins across membranes [6][7]. The largest application of proteases is in the detergent industry to remove protein-based stains from the cloths.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme used in the detergent had to be stable in a wide range of temperature and had to be active in the presence of various surfactants, bleaching agents, and various other additives. Currently, a large proportion of commercially available protease is derived from Bacillus strains and most of them were isolated from coastal regions [7][8][9][10][11]. From the study of the previous literature, it can be seen that due to the longest coastal region of Gujarat the possibility of getting the isolate with very good alkaline protease production is high [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Proteases are enzymes that catalyze the hydrolysis of peptide bonds, resulting in protein degradation into peptides and amino acids, and also can act in specific posttranslational modification reactions (Souza et al, 2015). Proteolytic enzymes stand out among the enzymes used for industrial applications, representing about 60 % of all commercial enzymes worldwide (Saggu et al, 2017). Proteases can be applied in different industrial sectors, including food industry, detergent additives, textiles, pharmaceuticals, waste treatment, diagnostic reagents, medical application, leather tanning and silver recovery (Marathe et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%